Molecular, Behavioral, and Physiological Consequences of Methamphetamine Neurotoxicity: Implications for Treatment - Moszczynska, Anna; Callan, Sean Patrick (The Journal of pharmacology and experimental therapeutics, 2017)
Understanding the relationship between the molecular mechanisms underlying neurotoxicity of high-dose methamphetamine (METH) and related clinical manifestations is imperative for providing more effective treatments for human METH users. This article provides an overview of clinical manifestations of METH neurotoxicity to the central nervous system and neurobiology underlying the consequences of administration of neurotoxic METH doses, and discusses implications of METH neurotoxicity for treatment of human abusers of the drug.